2012
DOI: 10.1071/rj11037
|View full text |Cite
|
Sign up to set email alerts
|

Social implications of bridging the gap through ‘caring for country’ in remote Indigenous communities of the Northern Territory, Australia

Abstract: ‘Caring for country’ is a term used to describe the complex spiritual affiliation that encompasses the rights and responsibilities that Aboriginal Australians have with their land. It includes their custodial responsibilities for keeping the land healthy and its species abundant. This ontology and associated practice of ‘caring for country’ continues across large sections of the Northern Territory of Australia through customary practice and through the Indigenous Ranger Program. This Program has been described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…V. Sinnamon's perspective reflects a deep commitment to the right of Kowanyama people to govern and manage their own estates, but also to indigenous NRM and cultural landscape management as important forms of contemporary work, both in terms of maintaining ecologically-valuable landscapes and in promoting sustainable indigenous livelihoods in remote areas. Contemporary NRM is an increasingly important component of indigenous peoples' relationships with their country, particularly in regional and remote areas (Larsen 2008;Altman and Kerins 2012;Gorman and Vemuri 2012). Formalised NRM agencies and funding provides resources and opportunities for people to visit and care for places that matter to them, but in doing so it affects the timing of visits, the activities undertaken and the landscape features that receive priority.…”
Section: Project Aims and Key Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…V. Sinnamon's perspective reflects a deep commitment to the right of Kowanyama people to govern and manage their own estates, but also to indigenous NRM and cultural landscape management as important forms of contemporary work, both in terms of maintaining ecologically-valuable landscapes and in promoting sustainable indigenous livelihoods in remote areas. Contemporary NRM is an increasingly important component of indigenous peoples' relationships with their country, particularly in regional and remote areas (Larsen 2008;Altman and Kerins 2012;Gorman and Vemuri 2012). Formalised NRM agencies and funding provides resources and opportunities for people to visit and care for places that matter to them, but in doing so it affects the timing of visits, the activities undertaken and the landscape features that receive priority.…”
Section: Project Aims and Key Conceptsmentioning
confidence: 99%
“…Working Knowledge explicitly references the utilitarian and pragmatic nature of contemporary indigenous NRM work, which is increasingly reliant upon external-funding regimes and focussed on (auditable) results overseen by non-local institutions and bureaucratic governance structures (Smith 2005;Gorman and Vemuri 2012). Yet Working Knowledge also references past histories of work (including subsistence activities often invisible to the cash economy), highlighting the continuities of these increasingly formalised activities with a longer historical process of material and economic engagement with the landscape.…”
Section: Working Knowledgementioning
confidence: 99%
“…Nevertheless, government and traditional owner agendas can be hard to reconcile , 2012, Smyth 2011, Gorman and Vemuri 2012. One in-depth analysis (Walker 2011) found that traditional owners and partners who participated in a review of management effectiveness of the Northern Tanami IPA agreed that management should give priority to objectives that are of prime importance to traditional owners.…”
Section: Development Of Ipa Management Plansmentioning
confidence: 99%
“…Traditional owners also seek economic outcomes from their country, such as an abundance of animal species that are valued as food (Wilson et al 2004), paid work that engages young people with traditional estates (Luckert et al 2007, Sithole et al 2008, Gorman and Vemuri 2012, and payment to elders for their cultural leadership and IEK teaching roles (Douglas 2011). The Australian Government's IPA Program takes advantage of the interface between these longstanding aspirations and government goals for biodiversity conservation Smyth 2003, Gilligan 2006).…”
Section: Indigenous Land Rights and Livelihoodsmentioning
confidence: 99%
See 1 more Smart Citation